2008
DOI: 10.1002/ppul.20777
|View full text |Cite
|
Sign up to set email alerts
|

The role of IL‐6 and IL‐11 in hyperoxic injury in developing lung

Abstract: We examined the cytoprotective effect of interleukin-6 (IL-6) and interleukin-11 (IL-11) during oxidant injury in neonatal lung and the regulators of cell death in vitro and in vivo after oxidant exposure. Type II cells from day 21 fetal neonatal rat lungs were treated with varying concentrations of either IL-6 or IL-11 for 24 hr prior to exposure to H(2)O(2). Three-day-old transgenic lung-specific IL-11 and IL-6 overexpressing and wild type (WT) mouse pups were exposed to hyperoxia or room air for 3 days. Typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
5
1
Order By: Relevance
“…The role of IL-6 in neonatal lung injury, however, has been controversially discussed. While overexpression of IL-6 aggravated lung injury in newborn mice that were exposed to hyperoxia after birth, IL-6 overexpression provides protective effects against oxidant-mediated injury when mice are exposed to hyperoxia from day [28,29]. In contrast, the present study demonstrates that Il6 null mice exhibit a mild reduction of alveoli already under normoxia that could be related to reduced number of myofibroblasts and possibly impaired secondary septation.…”
Section: Discussioncontrasting
confidence: 57%
“…The role of IL-6 in neonatal lung injury, however, has been controversially discussed. While overexpression of IL-6 aggravated lung injury in newborn mice that were exposed to hyperoxia after birth, IL-6 overexpression provides protective effects against oxidant-mediated injury when mice are exposed to hyperoxia from day [28,29]. In contrast, the present study demonstrates that Il6 null mice exhibit a mild reduction of alveoli already under normoxia that could be related to reduced number of myofibroblasts and possibly impaired secondary septation.…”
Section: Discussioncontrasting
confidence: 57%
“…We observed that mRNA of Ccl8 (MCP-2), Spp1 (osteopontin), Cxcl9 (Mig), IL1r2, Ccr5, Ccl24, and Itgam (CD11b, Mac-1) were increased and IL11 and Ccr7 were decreased by TiO 2 NPs. All these genes are probably relevant to the inflammation observed: Ccl8 is a well-known chemotactic agent for monocytes (32), Spp1 has a role in immune regulation and has Th1-cytokine functions (38), Cxcl9 is inducible in macrophages in response to interferon-␥ and may play a role in T cell trafficking (24), IL1r2 inhibits IL-1 activity by acting as a decoy target for IL-1 (11) (suggesting that its increase may be compensatory rather than contributory to pathology), Ccr5 is a receptor for MIP-1␣ and -1␤ and is known to have a role in lung inflammation (5), Ccl24 is strongly chemotactic for eosinophils (43), and Itgam is important in neutrophil recruitment to the lung (26), whereas IL-11 (9) and Ccr7 (13), which were decreased, are known to have a protective role in lung injury and inflammation. We also observed that protein amounts of multiple proinflammatory cytokines (e.g., eotaxin, G-CSF, IL-1␤, IL-2, IL-4, IP-10, M-CSF, MIP-1␣, MIP-1␤, MIP-2, TNF-␣) were increased with TiO 2 NP exposure, whereas VEGF was decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Proinflammatory cytokines do not cross the placenta [66] . There is convincing experimental and clinical data which indicate that the profound proinflammatory cytokine response present in the airways and pulmonary tissue of preterm infants may reflect an inability to regulate inflammation through an adequate expression of the anti-inflammatory cytokines IL-4, IL-10, IL-11, IL-12, IL-13, IL-18 or IL-1 receptor antagonist [1,5,[67][68][69] . Cellular IL-10 mRNA was undetectable in most airway samples of preterm infants with BPD, but it was expressed in all term infants with respiratory failure [67] .…”
Section: Pro-and Anti-inflammatory Cytokinesmentioning
confidence: 99%